Humorality in Early Modern Art, Material Culture, and Performance
XIV, 207 p. 11 illus., 10 illus. in color.
Keywords: Humorality in Early Modern Art, Material Culture, and Performance seeks to address the representation of the humors from non-traditional, abstract, and materialist perspectives, considering the humorality of everyday objects, activities, and performance within the early modern period. To uncover how humoralism shapes textual, material, and aesthetic encounters for contemporary subjects in a broader sense than previous studies have pursued, the project brings together three principal areas of investigation: how the humoral body was evoked and embodied within the space of the early modern stage; how the materiality of an object can be understood as constructed within humoral discourse; and how individuals’ activities and pursuits can connote specific practices informed by humoralism. Across the book, contributors explore how diverse media and cultural practices are informed by humoralism. As a whole, the collection investigates alternative humoralities in order to illuminate both early modern works of art as well as the cultural moments of their production. Amy Kenny teaches at University of California, Riverside, USA, and has a PhD in early modern literature and culture. Her first monograph, entitled Humoral Wombs on the Shakespearean Stage (Palgrave Macmillan), was published in 2019. Kaara L. Peterson is Associate Professor of English at Miami University of Ohio, USA. Her books include Popular Medicine, Hysterical Disease, and Social Controversy in Shakespeare's England (2010) and, with Deanne Williams, The Afterlife of Opheila (Palgrave Macmillan 2012).